Understanding Arab social TV viewers’ perceptions of virtual reality acceptance - Mohammed Habes; Mokhtar Elareshi; Amjad Safori; Amer Khaled Ahmad; Waleed Al-Rahmi; Javier Cifuentes-Faura (Cogent Social Sciences)
Social TV has become a part of contemporary functioning and viewing patterns. It enhances the television watching experiences of audiences and introduces new trends that can communicate different viewers. This study examines the social TV experiences of Jordanian young audiences regarding using virtual reality (VR) acceptance to understand their real-time experiences. A cross-sectional study design with randomly selected 354 individuals from Jordan was analysed utilizing the Structural Equation Modelling (SEM) to also examine the strength of every factor regarding VR used for social TV. Results showed four factors were directly linked to watching social TV (experiences, real-time, digital content, face-to-face communication). Therefore, the study also concluded that the prominent role of VR in enhancing social TV experiences regarding factors, e.g., entertainment, communication, and information sharing, its impact is a complex phenomenon, however.